DIGITALIZATION, SERVICE QUALITY, AND RELIGIOSITY IN SHAPING ZAKAT PREFERENCES: THE MEDIATING ROLE OF TRUST - Sauri, Supian; Jamalie, Zulfa; Wibowo, Fasih (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study examines the influence of service quality, religiosity, zakat knowledge, and digitalization on the zakat payment preferences of muzakki (people who pay zakat) and investigates the mediating role of trust in shaping these preferences within the Banjar community of South Kalimantan, Indonesia. Employing a quantitative field research design, data was gathered through structured questionnaires distributed to muzakki who pay zakat through formal institutions. Using purposive sampling, 500 questionnaires were distributed to muzakki across Banjarmasin, Banjarbaru, and Banjar Regency, yielding 397 responses, of which 201 were deemed valid for analysis. The findings reveal that service quality, religiosity, and digitalization have a significant direct effect on zakat preferences, while zakat knowledge does not exhibit a direct influence. Notably, trust serves as a mediating variable, enhancing the impact of service quality, religiosity, zakat knowledge, and digitalization on muzakki's zakat preferences. These results underscore the pivotal role of trust in encouraging the use of formal zakat institutions. This study contributes to the existing literature by introducing trust as a mediating factor offering a nuanced understanding of its role in the zakat ecosystem and by highlighting the growing relevance of digitalization in influencing contemporary zakat behavior.